2016
DOI: 10.1002/rcm.7600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HCl pretreatment, drying, and storage on the stable isotope ratios of soil and sediment samples

Abstract: HCl pretreatment effectively eliminates carbonates and thereby helps δ(13) C analysis of the organic fraction. HCl pretreatment is not recommended for δ(15) N and δ(34) S analysis. Freeze-drying of samples is recommended rather than oven drying. A temperature-dependent change in the isotopic ratios of long-term stored samples was observed during this study; therefore, relatively short-term storage (-80°C) of freeze-dried samples is preferable. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…The error associated with the HCl pre-treatment systematically decreases the measured δ 15 N by up to 4 . Therefore, enrichment at Friis Hills represents a minimum estimate (Kim et al, 2016). The δ 15 N values are similar to those found in fauna of the Antarctic Peninsula (e.g.…”
Section: The Mid-miocene Tundra Environmentsupporting
confidence: 77%
See 1 more Smart Citation
“…The error associated with the HCl pre-treatment systematically decreases the measured δ 15 N by up to 4 . Therefore, enrichment at Friis Hills represents a minimum estimate (Kim et al, 2016). The δ 15 N values are similar to those found in fauna of the Antarctic Peninsula (e.g.…”
Section: The Mid-miocene Tundra Environmentsupporting
confidence: 77%
“…The results are expressed in δ notation, which corresponds to the parts per thousand difference of 13 C/ 12 C with respect to the Vienna Pee-Dee Belemnite (VPDB) standard and 15 N/ 14 N with respect to the air (AIR) standard. A large error of ±4 was attributed to the δ 15 N results due to the possible effects of the HCl pre-treatment (Kim et al, 2016), but results are still presented to identify relative trends (variation within sample distribution > 4 ). Multiple comparison analyses were conducted in MATLAB R2018a(9.4.0.813654).…”
Section: 24mentioning
confidence: 99%
“…They confirmed this method as the most appropriate acid treatment for decarbonation. With regard to the effects of acid concentration, Kim et al reported that the optimum concentration of HCl required to remove inorganic carbon from samples was 1 mol/L. In this study, 1 mol/L HCl was used to treat the reference material (IAEA‐CH‐6) and some samples.…”
Section: Discussionmentioning
confidence: 88%
“…Homogenized powder samples of each tissue were decalcified with 1N HCl for at least 24 h to remove possible carbonates. However, subsamples for δ 15 N analysis were not treated with acid because it has been reported that HCl treatment affects δ 15 N values [ 36 ]. After the acid treatment, the samples were re-dried using a freeze drier and were ground to a fine powder, which was thoroughly mixed prior to analysis.…”
Section: Methodsmentioning
confidence: 99%